Kontribusi Gaya Kepemimpinan Kepala Sekolah, Etos Kerja, Disiplin Kerja, dan Supervisi Pendidikan Terhadap Profesionalisme Guru di SMP Tunas Daud Denpasar - D.A. Kakomore; K.R. Dantes; I.G.K.A. Sunu (Pascasarjana Universitas Pendidikan Ganesha, 2022)
This study aimed to determine: (1) the contribution of the principal's leadership style to teacher professionalism, (2) the contribution of work ethic to teacher professionalism, (3) the contribution of work discipline to teacher professionalism, (4) the contribution of educational supervision to teacher professionalism, (5 ) the contribution of the principal's leadership style, work ethic, work discipline, and educational supervision together to teacher professionalism at Ju inior High School of Tunas Daud Denpasar. The population in this study was 31 teachers. This study employed an ex-post facto design. Data were collected through questionnaire with a Likert scale model. The data analysis tech iniques used were simple regression, simple correlation, multiple correlation, multiple regression. The findings show that: (1) contributed positively and sig inificantly the principal's leadership style to teacher professionalism by 0.217, with an effective contribution of 5,425%, (2) contributed a sig inificant positive work ethic to teacher professionalism by 0.693, with an effective contribution of 39,224%, (3) contributing a sig inificant positive work discipline to teacher professionalism by 0.276 with an effective contribution of 7,176%(4) contributing sig inificant positive supervision of education towards teacher professionalism of 0.584 with an effective contribution of 21,55%, and (5) contributed sig inificantly to the principal's servant leadership, work ethic, work culture, and orga inizational commitment together to teacher professionalism with an effective contribution of 73,4%. This means that the four variables have a sig inificant contribution to the profession of teacher at Tunas Daud Denpasar Ju inior High School.